Guías para programas de mejora de la calidad en el trauma (Distribuna, 2012)
It is appropriate that the Pan American Trauma Association have a major textbook on trauma. Members of this association have not only cared for thousands and thousands of injured patients, but also have significantly contributed to the education of others in the discipline of trauma through formal in-hospital training programs, presentations at national meetings, and the written word. Trauma, the word and the disease, is endemic in all of our societies, regardless of our country of origin.